Social Dynamics of the Minang Ethnic Diaspora in Japan: Case Study of Japanese Literature Graduates of Universitas Bung Hatta - Dewi Kania Izmayanti; Syahrial Syahrial; Nolia Sri Wahyuni (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The purpose of this study is firstly to know and describe how the diaspora Alumni of the Japanese Literature Study Program of Universitas Bung Hatta live in Japan. Then, secondly, the purpose of this study is to know whether the language and culture that they studied at the University are useful in their life in Japan. The formulation of the problems that want to be studied is the impression felt when first arriving in Japan, the related learning of Japanese language and culture in living life in Japan, and what kind of living life by diaspora alumni of Japanese literature Minang ethnic in Japan. The methods used in this study are qualitative descriptive utilising questionnaires and structured interviews. The number of identified respondents is 29. The questionnaires were constructed in Google Forms, distributed through social media: WhatsApp. The data were then analysed using interpretative descriptive models. The analysis suggested that the obstacles experienced by Japanese Literature alumni from Minang ethnic diaspora in Japan when they first arrived in Japan were language and food. This is due to their lack of training in using Japanese when they were in college, and as ethnic Minangs, they cannot escape the taste of Minang cuisine. While related to the learning of Japanese language and culture, the material that has been given is felt quite helpful and quite used in, as well as the Japanese language that the diaspora uses, during living life in Japan, the Minang ethnic diaspora cannot be separated from consuming Indonesian cuisine or food, because this is also supported by the ease of obtaining Indonesian food and cuisine. This study finding is expected to add insight into the life of the Indonesian diaspora in Japan and can be a reference for further research related to the Indonesian diaspora.